IMPLEMENTASI MULTI SENSORY BRANDING PADA PERANCANGAN INTERIOR PALACE FINE CUISINE & BALLROOM (Jurnal PATRA, 2024)
The food and beverage industry in Indonesia continues to grow. This happens on the basis of changes in lifestyle and consumer behavior of society. Today, people have a habit of eating in restaurants with attractive interiors. Not only the quality of food, the experience of eating dishes is now also prioritized. Culinary entrepreneurs in responding to these changes are required to develop creative business strategies in creating a satisfying dining experience. The purpose of this design is to design the interior of the Palace Fine Cuisine & Ballroom by applying the Multi Sensory Branding Technique to create a unique dining experience. This technique stimulates the human senses to increase imagination and perception, thereby creating an emotional bond between brands and consumers. This design method is Design Thinking with six stages, namely Understand, Observe, Point of View, Ideate, Prototype, and Test. The result of this design is the interior design of the Palace Fine Cuisine & Ballroom with the application of Multi Sensory Branding, which is implemented in each room specifically according to the purpose and function. Multi Sensory Branding is proven to be able to create emotional bonds with customers through the results of several respondents' responses to design prototypes.